Faktor Faktor Yang Berhubungan dengan Safe Staffing di Rumah Sakit - Hardi, Deni Er; Yulia, Sri; Muliyadi, Muliyadi (Jurnal Berita Ilmu Keperawatan, 2019)
Background : The availability of nursing resources, conducive work atmosphere for nurses and creating safe health service are the factors related to safe staffing. If one of these three aspects is not fulfilled, it can cause low health service quality given by the hospital. The Objective : To identify the factors related to safe staffing at X Palembang Hospital in 2017. Method : This study is a quantitative study using cross sectional survey. The samples were taken by applying total sampling method, there were 48 nurses taken as the respondents. Result : Nurses' perception concerning with the availability of nursing resources was categorized good with 24 respondents (50%), conducive work atmosphere was categorized good with 30 respondents (62,5%), creating safe health service was categorized good with 35 respondents (72,9%), and safe staffing was categorized good with 32 respondents (66,7%). There was a significant correlation between the availability of nursing resources and safe staffing (p value=0,001), there was a significant correlation between conducive work atmosphere and safe staffing (p value=0,027), and there was a significant correlation between creating safe health service system and safe staffing (p value=0,000). Conclusion and Suggestion : It is very important that Hospital apply safe staffing. Nursing department together with Hospital Safety Committee can develop the plan to increase human resources quality by giving training in accordance with nurses' competence, giving reward to nurses, and improving the employees' status.